Analysis of the Effectiveness of the Internal Audit Function in Enhancing Good Governance by the Supervisory Division of the High Prosecutor’s Office of North Sumatra - Jefri Ronaldo; Agus Tripriyono; Oktarini Khamilah Siregar (Jurnal Multidisiplin Indonesia, 2025)
This study examines the effectiveness of the integrated Electronic Chart Display and Information System (ECDIS) and Automatic Radar Plotting Aid (ARPA) in supporting navigational awareness during ship operations. The research aims to analyze how these systems are operationally utilized, how their integration enhances situational awareness, and how human factors influence their effectiveness—including potential limitations and risks associated with electronic navigation. A qualitative approach was employed, with data collected through onboard observations during actual voyages, semi-structured interviews with deck officers, and document analysis of navigation logs, passage plans, radar screenshots, ECDIS tracks, and company safety manuals. Data were analyzed using thematic content analysis to identify recurring patterns across observational data, interview transcripts, and documentation. The findings indicate that the integrated use of ECDIS and ARPA significantly supports navigational awareness by improving target tracking, route monitoring, and decision-making processes. However, system effectiveness is highly dependent on operator competence, situational judgment, and proper interpretation of electronic information. Overreliance on electronic systems, limited system understanding, and insufficient alarm management were identified as potential risks. The study concludes that while ECDIS and ARPA integration enhances navigational safety, continuous training, procedural discipline, and awareness of system limitations are essential to ensure effective and safe navigation.